Epigallocatechin‐3‐gallate augments therapeutic effects of mesenchymal stem cells in skin wound healing. (November 2016) - Li, Min; Xu, Jingxing; Shi, Tongxin; Yu, Haiyang; Bi, Jianping; Chen, Guanzhi
Summary: In non‐healing wounds, mesenchymal stem cell (MSC)‐based therapies have the potential to activate a series of coordinated cellular processes, including angiogenesis, inflammation, cell migration, proliferation and epidermal terminal differentiation. As pro‐inflammatory reactions play indispensable roles in initiating wound repair, sustained and prolonged inflammation exhibit detrimental effects on skin wound closure. We investigated the feasibility of using an antioxidant agent epigallocatechin‐3‐gallate (EGCG), along with MSCs, to improve wound repair through their immunomodulatory actions. In a rat model of wound healing, a single dose of EGCG at 10 mg/kg increased the efficiency of MSC‐induced skin wound closure. Twenty days after the wound induction, MSC treatment significantly enhanced the epidermal thickness, which was further increased by EGCG administration. Consistently, the highest extent of growth factors upregulation for neovascularization induction was seen in the animals treated by both MSCs and EGCG, associated with a potent anti‐scarring effect throughout the healing process. Finally, expression levels of pro‐inflammatory cytokines, such as tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β) and IL‐6, in the wound area were reduced by MSCs, and this reduction was further potentiated by EGCG co‐administration. EGCG, together with MSCs, can promote skin wound healing likely through their combinational effects in modulating chronic inflammation.